IMPLEMENTATION OF PATIENT SERVICES IN THE EMERGENCY INSTALLATION OF PORSEA REGIONAL PUBLIC HOSPITAL - Siska Tuanita L. Tobing; Bambang Fitrianto (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Emergency Services are medical actions needed by emergency patients immediately to save lives and prevent disability. The problems in this study include how the legal relationship between doctors and patients in the Emergency Installation medical services according to health law in Indonesia, how the implementation of medical services to patients in the Emergency Room of the Porsea Regional General Hospital, and what form of legal protection regarding the actions of doctors in providing patient services in the Emergency Room of the Porsea Regional General Hospital. This study uses an empirical legal method with a descriptive analysis approach. Data were obtained through interviews, observations, and legal document studies. The legal relationship between medical and health personnel and patients in medical services in the emergency installation of a hospital according to health law in Indonesia is based on the principle that informed consent must be obtained before medical action is taken, especially in an emergency. The implementation of medical services for patients in the Emergency Room of Porsea Regional General Hospital has generally referred to a well-structured SOP, starting from the triage process to assess the patient's level of emergency to medical and administrative treatment. The form of legal protection for the actions of doctors in providing patient services in the Emergency Room (IGD) of Porsea Regional General Hospital focuses on the doctor's obligation to act quickly and appropriately in emergency situations, even though the patient cannot provide direct consent. Porsea Regional General Hospital also provides legal protection through the socialization of medical ethics and law, legal assistance for medical personnel in the event of a medical dispute, and a good documentation system to ensure that all medical actions are in accordance with applicable operational standards and procedures. Researchers recommend improving understanding of health law and therapeutic communication by medical personnel, periodic evaluation of SOPs by hospitals, and routine training on legal and ethical aspects of medicine, especially regarding the handling of emergency patients without consent to improve the quality and protection of services.